Rhyming dust bunnies - Thomas, Jan, 1958- (Atheneum Books for Young Readers, 2009)
As three dust bunnies, Ed, Ned, and Ted, are demonstrating how much they love to rhyme, a fourth, Bob, is trying to warn them of approaching danger.